No barriers to investment in electricity and gas distribution grids through incentive regulation - Astrid Cullmann; Nicola Dehnen; Maria Nieswand; Ferdinand Pavel (DIW Economic Bulletin, 2015)
Since early 2009, electricity and gas distribution in Germany has been subject to incentive regulation designed to ensure greater efficiency in electricity and gas grid operation. However, it remains to be seen how changes to the regulatory framework will affect the investment behavior of distribution system operators. Against this background, the present study empirically analyzes the investment activities of distribution system operators for the period from 2006 to 2012. The key questions are whether the introduction of incentive regulation in 2009 has had an empirically demonstrable impact on investment and whether this effect is due to the introduction of incentive regulation per se, or to its specific design. The findings show a positive effect on investment since the introduction of incentive regulation which, in particular, is determined by the specific design of regulation.
Keywords: D22; L51; L94; L95; 330; Investments; Regulation; Network Industries